A prospective study of sleep status, anxiety, and depression levels of college students at a university in Shandong Province, China - Zhang, Chengshuai; Zhao, Ling; Dong, Tingting; Zhao, Ji; Gao, Cui; Zhao, Feng (Frontiers in Psychology, 2024)
Objective To investigate the changes in sleep conditions, anxiety, and depression levels among college students before and after entering the university. Methods Utilizing a random sampling method, 692 new students from a college in Shandong province were selected in September 2019, and relevant indices were statistically analyzed in September 2021 following a comprehensive follow-up. Sleep status, anxiety, and depression levels were assessed using the Pittsburgh Sleep Quality Index (PSQI), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7), respectively. Results Gender, passive smoking, exercise, intake of fruits, and intake of seafood were identified as significant influencing factors on college students’ sleep status, anxiety, and depression levels (p < 0.05). A substantial difference was observed in the sleep quality of college students between the early enrollment stage and the follow-up stage (p < 0.05). Moreover, a significant positive correlation was found between PSQI scores and the levels of anxiety and depression (p < 0.05), cumulatively explaining approximately 10% of the variance in anxiety and depression levels. Conclusion The sleep quality of college students exhibited significant improvement after enrollment compared to the early enrollment period. Engaging in appropriate exercise and consuming fruits and seafood demonstrated a positive impact on sleep conditions, anxiety, and depression levels. These findings underscore the importance of fostering healthy lifestyle habits for promoting overall well-being among college students.